ANALISIS PENGARUH INFLASI TERHADAP PROFITABILITAS BANK UMUM SYARIAH DEVISA DI INDONESIA - Fida Arumingtyas; Lisdewi Muliati (Prosiding Simposium Nasional Multidisiplin (SinaMu), 2019)
This research is performed in order to test the influence of the variable Inflation rate toward Return On Asset (ROA) on Islamic Comercial Bank Foreign Exchange at 2016-2019 period. Analysis technique used is linear regression which is inflation rate as independent variable and ROA as dependent variable. The result of this research conclude that the inflation rate is not significantly influence Return On Asset (ROA).Keyword : ROA, inflation, islamic comercial bank foreign exchange.